Applications of modeling of structural equations in nursing: integrative review - Juliane Umann; Rodrigo Marques da Silva; Cristilene Akiko Kimura; Liana Lautert (Universidade Federal de Goias, 2017)
We analyzed the scientific production using modeling of structural equations in nursing. We conducted an integrative review in June of 2016 in the databases PUBMED, MEDLINE, and LILACS. We identified 127 articles, and we selected 20 from those. We conducted the analyses - quality and level of evidence - using validated tools and a synoptic table. The articles attended to 80% of STROBE items (95%), level of evidence 5 (95%) and published in Asian (50%) and North American (30%) countries. There was an increase of the scientific production using models of structural equations during the study period and the predominance of investigations aimed at the work organization. The use of modeling of structural equations in nursing is growing. However, studies aimed at assistance and teaching are lacking. This method appeared useful for issues in research in this health field.